Exploring the teaching and learning process among deaf students by using images / Aidah Alias - Alias, Aidah (2014)
Education is one of the most important fundamental elements in a human life. It helps us in learning and achieving new things in life. The ability of hearing gave us chances to hear voices and it is important in our communication. But, what if we are born deaf or having hearing loss while growing up? It have been stated clearly by other researchers, the possibility students faced with conflicts is when they learn and faced with the inappropriate learning style. Problems occur when students' learning styles cannot be adapted with the style of teaching activities and lectures. As a result students become bored and do not concentrate; cause them to fail to get high marks in examinations, less interested in a particular subject and then give up. The objectives of this study are to identify the current practice in teaching and learning among deaf students and to analyse appropriate teaching model of using images in enhancing learning process among deaf students. A case study method was employed by using methods of observation and interviews to selected deaf students and teachers. The findings indicated that the induction is the current practice in teaching and learning among deaf students and suitable method of teaching for deaf students is by using images and movement. In other words by combining these two medium of images and movement, this study suggested the best medium is by using sequential images. The study concluded and recommended that sequential image model is the recommended medium to be used in teaching and learning process for deaf students.